The links between agriculture and health: an intersectoral opportunity to improve the health and livelihoods of the poor - Corinna Hawkes; Marie Ruel (The World Health Organization, 2006)
Agriculture and health are linked in many ways. First, agriculture is essential for good health: it produces the world's food, fibre and materials for shelter; in many countries it is also an important source of livelihood among the poor. At the same time, agriculture can be linked with poor health, including malnutrition, malaria, foodborne illnesses, human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), livestock-related diseases, chronic diseases and occupational ill-health. Health also affects agriculture: people's health status influences the demand for agricultural outputs, and in agricultural communities, poor health reduces work performance, reducing income and productivity and perpetuating a downward spiral into ill-health. This paper presents an overview of the bidirectional links between agriculture and health with a focus on the developing world. It develops a conceptual framework that brings together the various links between agriculture and health into a single broad framework. The framework comprises the core components of the agricultural supply chain (producers, systems and outputs), key health concerns and the mechanisms of common interaction between the agricultural and health components: income, labour, environment and access - all key social determinants of health. These links between agriculture and health present an opportunity for the two sectors to work together to find solutions to each other's problems. Yet the health and agricultural sectors remain poorly coordinated. Leadership from global health and agricultural institutions is needed to build policies and good governance to facilitate integration, while capacity building is needed at all levels to help translate the conceptual links into comprehensive action on the ground. Health and agricultural researchers likewise need to work more closely together to achieve common goals.